Recent Advances in Synthesis and Properties of Pyrazoles - María-Camila Ríos; Jaime Portilla (Chemistry, 2022)
Pyrazole-containing compounds represent one of the most influential families of N-heterocycles due to their proven applicability and versatility as synthetic intermediates in preparing relevant chemicals in biological, physical-chemical, material science, and industrial fields. Therefore, synthesizing structurally diverse pyrazole derivatives is highly desirable, and various researchers continue to focus on preparing this functional scaffold and finding new and improved applications; this review highlights some of the most recent and strategic examples regarding the synthesis and properties of different pyrazole derivatives, mainly reported from 2017–present. The discussion involves strategically functionalized rings (i.e., amines, carbaldehydes, halides, etc.) and their use in forming various fused systems, predominantly bicyclic cores with 5:6 fusion taking advantage of our experience in this field and the more recent investigations of our research group.